A new perspective on meals as part of an Optimized Mixed Diet for children and adolescents - Kersting, Mathilde; Kalhoff, Hermann; Sinningen, Kathrin; Lücke, Thomas (Frontiers in Nutrition, 2022)
Objectives To show by the example of the Optimized Mixed Diet (OMD) for children and adolescents in Germany, how the different food and nutrient profiles of the traditional daily meals complement each other to achieve daily nutrient intakes that meet the Dietary References V. Methods The 7-day menu plan of the OMD with the usual 5 daily meals in Germany was used. The total nutrient intake from all meals was compared with the nutrient references. Then the composition of the meals was optimized. Results Although the cooked meal (lunch) provides only 25% of the daily energy intake, it is relatively rich (>25% of the daily intake) in most vitamins and minerals, which distinguishes it from the other meals. The cold main meals (breakfast, dinner) are rich in calcium and vitamin B2, due to the preferential use of milk in these meals. The two snacks each provide 12.5% of the daily energy intake. Discussion and conclusion People eat foods but not nutrients and they eat foods as meals; this holds especially true for children and adolescents. A well-calculated menu plan can assure the nutrient adequacy of an OMD where the different food and nutrient profiles of the meals complement each other in a modular system. Guidelines for meals could facilitate flexible coordination of family meals and meals in childcare centers and schools. Different meal types set varied stimulus patterns at different levels (neurocognition, emotion, digestion), which may open up long-term health benefits.